FORMATION OF ARTISTIC AND IMAGINATIVE THINKING AMONG PEDAGOGICAL UNIVERSITY STUDENTS IN THE PROCESS OF STUDYING PROGRAM WORKS BY UZBEK COMPOSERS IN PIANO LESSONS - Adela Trigulova (The Bioscan, 2025)
The article examines the process of formation of artistic and figurative thinking of students of pedagogical universities in the process of studying works of Uzbek composers in piano lessons. KEYWORDS: Musical image, pianist’s thinking, memory, associations, content of the piece.